Measuring the Motivational Work Environment Level At Saudi Universities in Makkah Region - Aljhany, Faddia; Al-Otaibi, Saad (The Arab Journal of Administration, 2024)
With considering the rapid changes in the business world, as well as Vision 2030, which calls for an adoption of new, more advanced tools and visions, educational institutions have encountered many challenges that they must integrate with, to achieve suitable outcomes to meet the needs of the labor market. The aim of the study was to measure the level of motivational work environment at universities in the Makkah region. The research was conducted using a descriptive analytic approach, and the questionnaire as a primary tool for research. The research sample consisted of faculty members, which numbered (139) individuals. Among the most important findings were that the study sample were neither agreeing nor disagreeing to the work environment dimension with percentage (57.3%), (57.3%) for the physical environment dimension, and (64.7%) for the working relations dimension at Saudi universities in Makkah region. According to the research findings, the study recommended that faculty members and senior management to be more engaged in the decision-making process and to open appropriate communication channels for feedback. Also, the study highlighted the need of promoting educational environment by improving the quality of academic facilities in a way that enhances the motivational work environment. In addition, providing opportunities for faculty members to attend conferences and seminars to improve their academic and research skills.